ANALISIS BREAK EVENT POINT PADA PERENCANAAN LABA TOKO LITTLE DINO PONTIANAK - Febriyanti, Indah; Warneri, Warneri; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was conducted on the road Teuku Umar, Pontianak Mall Block C36 Complex. The purpose of this research is to find out the break event point analysis at the Little Dino Pontianak Shop. This research method is qualitative research with a case study method, which is meant by providing an overview of break event points as sales profit planning at the Little Dino Pontianak Shop. The data source used in this research is the owner or leader of the Little Dino Pontianak Shop, and the data is from observations, interviews and documentation with the owner. From the results of the analysis carried out in this research, it can be concluded that the Little Dino Pontianak Shop in planning profits has not used BEP calculations, because it has not separated fixed costs and variable costs, making it difficult for management to carry out the desired profit planning and cost monitoring. And the sales value that the Little Dino Shop Pontianak must achieve in 2022 so that it does not suffer a loss is 1) Rp. 69,359,674 in August by selling 1,138 units of product, 2) amounting to Rp. 75,348,664 in September by selling 1,236 units of product, and 3) Rp. 69,356,738 in October selling 1,288 units of product.